Diploid GA with Real-valued vs. Binary-coded Recombination Operator in Diploid Genetic Algorithm - Attea, Bara'a (Iraqi Journal of Science, 2025)
Different evolutionary algorithms based on real coding have been presented for tracking parameter optimization problems. They include evolution strategies (ESS) and real-coded genetic algorithms (RCGAS). As the power of the GAs arises from their recombination (crossover) operator, and it may be considered to be one of the components to be borne in mind to improve the GA's behavior, researchers on evolutionary algorithms considered a new class of recombination operators- called real-vahied recombination operators.. In this paper, we examine the celeet of real-valued recombination operator in diploid genetic algorithm, comparing its results with that of diploid genetic algorithm using bit-coding recombination operators.